2007
DOI: 10.1080/00207450601125840
|View full text |Cite
|
Sign up to set email alerts
|

High Interleukin-10 Production Is Associated With Anti-Acetylcholine Receptor Antibody Production and Treatment Response in Juvenile Myasthenia Gravis

Abstract: To investigate the significance of humoral immunological factors in juvenile myasthenia gravis (JMG) patients, 11 children with JMG (age of onset between 2 and 13 years) and 8 healthy controls were enrolled. Plasma IL-2, IL-10, IFN-gamma, TNF-alpha, complement factor C3, C4, and C1q levels were measured by ELISA. IL-2, IL-10, TNF-alpha, C3, and C4 levels were significantly elevated in the patient group. Moreover, plasma IL-10 levels were associated with the presence of anti-AChR antibody and response to treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…39 It has been found that MG patients had increased numbers of AChR-reactive IL-10 mRNA-expressing PBMCs. 4,40 High IL-10 levels were associated with AChR antibody production and treatment response in juvenile MG. 5 These findings support the hypothesis that IL-10 plays important roles in the pathogenesis of MG. The symptoms of MG are caused by the autoantibodies that attack the receptors in the postsynaptic muscle membrane, leading to muscle fatigue and weakness.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…39 It has been found that MG patients had increased numbers of AChR-reactive IL-10 mRNA-expressing PBMCs. 4,40 High IL-10 levels were associated with AChR antibody production and treatment response in juvenile MG. 5 These findings support the hypothesis that IL-10 plays important roles in the pathogenesis of MG. The symptoms of MG are caused by the autoantibodies that attack the receptors in the postsynaptic muscle membrane, leading to muscle fatigue and weakness.…”
Section: Discussionsupporting
confidence: 76%
“…Cytokines produced by immune cells are crucial regulators of the pathogenesis of MG. For example, cytokines such as interleukin (IL)-2, interferon (IFN)-g, and tumor necrosis factor (TNF)-a secreted by T helper (Th) cells stimulate the production of pathogenic antibodies, which are mediated by B cells. 3 Moreover, both the expression of cytokines, such as IL-2, IFN-g, and IL-10, and the number of peripheral blood mononuclear cells (PBMCs) secreting these cytokines are higher in patients with MG. [4][5][6] Increasing evidence shows that noncoding RNAs (ncRNAs) are involved in the regulation of gene expression in the immune system, and thus they provide novel insight into the pathogenesis, diagnosis, and treatment of MG. 7 Long ncRNAs (lncRNAs; more than 200 nt) interact with DNA, RNA, or proteins to modulate the expression of protein-coding genes, which play important roles in various biological processes, including the regulation of immune responses. 7 It has been reported that aberrant expression of lncRNA IFNG-AS1 in PBMCs regulates CD4 + T cell activation in MG patients partly by influencing human leukocyte antigen (HLA)-DRB1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a cohort of mostly seronegative juvenile MG patients with mild disease severity, serum C3 [4,20e25,27,28,30,32,33]. and C4 levels have been found to be elevated [39]. Overall, these results suggest that complement-mediated NMJ destruction might at least partially be involved in the pathogenesis of MG without conventional anti-AChR antibodies.…”
Section: Complement System In Musk Antibody Positive and Seronegative Mgmentioning
confidence: 82%
“…The higher NF‐κB levels, the higher TLR1 expression and the increased production of the pro‐inflammatory cytokines TNFα and CXCL10 previously found for the A allele could provide clues for the risk association we found for alloimmunization in SCD. The effect on IL10 is somewhat counterintuitive because this cytokine is known to augment antibody production and is associated with antibody‐mediated autoimmunity (Xu et al , ; Yapici et al , ; Wang et al , ). It would therefore be interesting to measure cytokine levels in SCD patients with this variant.…”
Section: Discussionmentioning
confidence: 99%